Dry powder mixture containing conductive agent and PVDF (Polyvinylidene Fluoride) as well as preparation method and application of dry powder mixture

By preparing a dry powder mixture containing conductive agent and PVDF, the difficulty in applying PVDF binder in dry electrode manufacturing and the problem of uneven dispersion of carbon black and PVDF were solved, and a dry powder mixture with low resistivity and low cohesion was achieved, which improved the performance of the electrode.

CN119331545APending Publication Date: 2025-01-21ZHEJIANG RES INST OF CHEM IND CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310883587.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-19
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In the prior art, PVDF binder is difficult to be used in dry electrode manufacturing processes, and carbon black and PVDF are difficult to disperse uniformly, resulting in high resistivity and large cohesion, which affects the performance of the electrode.

Method used

By preparing a dry powder mixture containing conductive agent and PVDF, the mass ratio of conductive agent to PVDF is 1:4 to 4:1. After ultrasonic crushing treatment, the average particle size D50 is <7 μm, the resistivity is ≤10-3Ω·m, and the shape is spherical. Degree D[4,3]/D[3,2]<4, and is prepared using an aqueous dispersion spray drying process.

Benefits of technology

It achieves uniform mixing of conductive agent and PVDF, reduces resistivity and cohesion, improves bonding strength and distribution of bonding sites, and is suitable for dry electrode manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331545A_ABST
    Figure CN119331545A_ABST
Patent Text Reader

Abstract

The invention discloses a dry powder mixture containing a conductive agent and PVDF and a preparation method and application thereof, the mass ratio of the conductive agent to the PVDF in the dry powder mixture is 1: 4-4: 1, the resistivity of the dry powder mixture is less than or equal to 10 <-3 > omega.m, the average particle size D50 of the dry powder mixture is less than 20 microns, and the average particle size D50 of the dry powder mixture is less than 7 microns after the dry powder mixture is subjected to ultrasonication treatment. The dry powder mixture serving as a binder is suitable for preparing an electrode by a dry process, the problem that a carbon black conductive agent and PVDF are difficult to uniformly disperse is solved, meanwhile, the dry powder mixture is better in conductivity and lower in particle cohesion and can be better mixed with an electrode active material in the dry process electrode manufacturing process, obvious fibrosis of PVDF can be seen in the prepared membrane, and the prepared membrane has a good application prospect. The bonding strength is higher, more bonding sites exist, and the tabletting strength is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymers, and in particular to a dry powder mixture containing a conductive agent and PVDF, and a preparation method and application thereof. Background Art

[0002] The wet electrode manufacturing process requires the use of solvents. The most commonly used solvent is NMP, which is a toxic solvent that needs to be recycled. In addition, the wet electrode manufacturing process requires a huge, expensive and complex electrode coating machine. The dry electrode manufacturing process is to mix the active material, conductive agent and binder evenly, form a self-supporting film under the fibrillation of the binder, and roll it on the surface of the current collector. Compared with the wet electrode manufacturing process, the dry electrode manufacturing process does not require the use of solvents.

[0003] Dry film making includes binder fibrillation method and electrostatic spraying method, among which binder fibrillation method is the mainstream, and electrostatic spraying method is inferior to binder fibrillation method in terms of processability, adhesion stability, electrode flexibility and durability. The binder fibrillation method is to add PTFE binder after mixing the active material powder with the conductive agent, and then apply external high shear force to the dry mixture to make the PTFE fibrillate and bond the electrode membrane powder, and finally extrude the mixture to form a self-supporting membrane.

[0004] As a common binder for wet electrodes, PVDF is difficult to fibrillate, and the adhesion effect after electrostatic spraying is poor. Therefore, PVDF is difficult to be used as a binder for dry electrodes. Patent document CN113889658A discloses the manufacture of a solvent-free electrode, using a PVDF aqueous binder dispersion sprayed on carbon black. During spraying, a powder / latex mist is mixed by a magnetic stirring bar. After drying in a vacuum oven, 5mm zirconia beads are used as grinding media to mix the dry mixture at 2000rpm in a centrifugal planetary mixer for 1min to break up large crumbs. Although this method obtains a mixture of PVDF and carbon black, there are problems such as complex preparation process and inability to industrialize and apply, and there is a problem of poor uniformity of PVDF and carbon black dispersion. At the same time, due to the high-energy impact of ball milling, the primary particles of PVDF emulsion are deformed to form agglomerated particles with high cohesion, which seriously affects the uniformity of subsequent mixing with active materials.

[0005] Conductive agents such as carbon black are prone to agglomeration during the preparation of battery pole pieces, making it difficult to achieve uniform dispersion. Patent document WO2023044754A1 discloses a conductive binder that polymerizes VDF by selecting a chain transfer agent with a specific structure. The binder can be used to perform surface grafting modification on carbon-based conductive agent particles to improve the problem of carbon-based conductive agents being prone to agglomeration when the slurry is stirred.

[0006] PTFE, a commonly used binder in the dry electrode manufacturing process, has poor polymer reduction resistance, which leads to poor initial efficiency and cycle performance of the battery. Therefore, in order to obtain a PVDF product for dry electrodes, further research is needed. Summary of the invention

[0007] Technical problem to be solved by the invention

[0008] The present invention is based on obtaining a PVDF binder suitable for dry electrode manufacturing. Its purpose is to solve the problem that PVDF binder cannot be used in dry electrode manufacturing process, and at the same time solve the problem that carbon black and PVDF are difficult to disperse evenly, so as to obtain a dry powder mixture containing a conductive agent and PVDF with low resistivity and low cohesion. When using it to manufacture electrodes by dry method, obvious fiberization of PVDF can be seen.

[0009] Technical solutions to solve problems

[0010] First, the present invention provides a dry powder mixture containing a conductive agent and PVDF, wherein the mass ratio of the conductive agent to the PVDF is 1:4 to 4:1, and the resistivity of the dry powder mixture is ≤10 -3 Ω·m, the average particle size D50 of the dry powder mixture is less than 20 μm, and after the dry powder mixture is subjected to ultrasonic crushing, the average particle size D50 is less than 7 μm.

[0011] The resistivity of the present invention is tested using a ST2732-SD powder resistivity tester, and the average particle size D50 is tested using a Mastersizer 3000 laser particle size analyzer.

[0012] The sphericity of the dry powder mixture of the present invention is D[4,3] / D[3,2]<4, preferably, D[4,3] / D[3,2]<2. The closer the values ​​of D[4,3] and D[3,2] are, the more regular the shape of the particles is and the more concentrated the particle size distribution is. D[4,3] represents the volume average particle size and D[3,2] represents the surface area average particle size, which are measured using a Mastersizer 3000 laser particle size analyzer.

[0013] The mass ratio of the conductive agent to PVDF of the present invention is determined according to the content of the conductive agent and PVDF required by the electrode sheet. Considering the conductivity and bonding performance of the electrode sheet, preferably, the mass ratio of the conductive agent to PVDF is 1:4 to 4:1, and more preferably, 3:7 to 1:1. When the electrode sheet meets the performance requirements, the less the amount of conductive agent used, the better, the lighter the weight, and the higher the energy storage content per unit weight.

[0014] The resistivity of the dry powder mixture of the present invention is ≤10 -2 Ω·m, preferably, resistivity ≤10 -3Ω·m, more preferably, the resistivity ≤10 -4 Ω·m. The resistivity value indicates the degree of mixing of the conductive agent and PVDF. The higher the resistivity value, the worse the mixing uniformity of the conductive agent and PVDF. The lower the resistivity value, the better the mixing uniformity of the conductive agent and PVDF.

[0015] The average particle size D50 of the dry powder mixture of the present invention is less than 20 μm, and after ultrasonic crushing, the average particle size D50 is less than 7 μm. Preferably, the average particle size D50 of the dry powder mixture is less than 10 μm, and after ultrasonic crushing, the average particle size D50 is less than 3 μm. More preferably, the average particle size D50 of the dry powder mixture is less than 5 μm, and after ultrasonic crushing, the average particle size D50 is less than 1 μm. The change in the average particle size of the dry powder mixture before and after ultrasonic crushing indicates the magnitude of the cohesion of the dry powder mixture particles. The greater the change in the average particle size of the dry powder mixture, the smaller the cohesion of the dry powder mixture particles, and the easier it is to disperse. When the dry powder mixture is used as a component in the preparation of electrode sheets, it is easier to be evenly dispersed with the electroactive material.

[0016] The conductive agent of the present invention is a conductive agent that can be used in the field of electrochemical energy storage. Preferably, the conductive agent is selected from at least one of carbon black SuperP, multi-walled carbon nanotubes, single-walled carbon nanotubes, graphene, acetylene black, superconducting carbon, Ketjen black, carbon dots, carbon nanofibers, superconducting carbon black, graphite, artificial graphite, carbon, carbon black, activated carbon, and carbon fiber. The lower the cohesion of the conductive agent, the easier it is to disperse. More preferably, the conductive agent is selected from at least one of carbon black SuperP, multi-walled carbon nanotubes, and single-walled carbon nanotubes. More preferably, the conductive agent is selected from carbon black SuperP.

[0017] The average particle size of the primary particles (i.e., primary particles) of the conductive agent of the present invention only needs to meet the requirements. Preferably, the average particle size of the primary particles of the conductive agent is 10 to 100 nm. More preferably, the average particle size of the primary particles is 20 to 60 nm. The smaller the particle size of the primary particles of the conductive agent, the more particles there are per unit volume, which is beneficial to improving conductivity and reducing resistivity, but the smaller the particle size, the more difficult it is to disperse.

[0018] The PVDF described in the present invention is a VDF homopolymer or a copolymer of VDF and other comonomers.

[0019] The comonomer is selected from at least one of fluoroethylene, trifluoroethylene, trifluorochloroethylene, 1,1-fluorochloroethylene, 1,2-fluorochloroethylene, tetrafluoroethylene, tetrafluoropropylene, pentafluoropropylene, hexafluoropropylene, perfluoroalkylethylene, perfluoroalkylvinyl ether, perfluoro-n-propylvinyl ether, perfluoromethylvinyl ether, perfluoro(2,2-dimethyl-1,3-dioxole), ethylene, acrylic acid, acrylate, methacrylic acid, methacrylate, 2-(trifluoromethyl)acrylic acid, 2-(trifluoromethyl)acrylate, 2-trifluoroethyl methacrylate, 1,1-difluoro-2-methyl methacrylate, vinyl ether, vinyl acetate, acrylonitrile, butadiene, isoprene, styrene, maleic anhydride or itaconic acid. Preferably, the comonomer is selected from at least one of fluoroethylene, trifluoroethylene, tetrafluoroethylene, hexafluoropropylene, acrylic acid, acrylate, 2-(trifluoromethyl)acrylic acid, 2-(trifluoromethyl)acrylate, acrylonitrile or vinyl ether. More preferably, the comonomer is selected from at least one of vinyl fluoride, trifluoroethylene, tetrafluoroethylene, hexafluoropropylene, acrylic acid, acrylic acid ester, 2-(trifluoromethyl)acrylic acid, 2-(trifluoromethyl)acrylate, acrylonitrile or vinyl ether. Further preferably, the comonomer is selected from hexafluoropropylene.

[0020] The content of VDF structural monomer in the PVDF of the present invention is 80-100 mol%, preferably 95-99.9 mol%.

[0021] The molecular weight of the PVDF of the present invention can be used in the field of electrochemical energy storage. Preferably, the viscosity of a 7 wt % NMP solution of the PVDF is 1 to 10000 Pa.s.

[0022] Further, for the dry electrode preparation process using a single PVDF binder, the solution viscosity of the 7 wt % PVDF NMP solution is 100 to 10000 Pa.s, preferably 500 to 5000 Pa.s, and more preferably 800 to 4000 Pa.s.

[0023] Furthermore, for the dry electrode preparation process using PVDF and PTFE binder, the solution viscosity of the 7 wt % PVDF in NMP solution is 1 to 100 Pa.s, preferably 20 to 50 Pa.s.

[0024] The PVDF of the present invention is prepared by a polymerization method commonly used in the art, such as aqueous free radical emulsion polymerization, suspension polymerization, solution polymerization, and supercritical CO 2Polymerization. Preferably, aqueous free radical emulsion polymerization is used for preparation. In conventional emulsion polymerization, deionized water, a water-soluble surfactant capable of emulsifying the reactant mass during polymerization, and an optional paraffin antifouling agent are loaded into the reactor. The mixture is stirred and deoxygenated. Then a predetermined amount of chain transfer agent and other auxiliary agents are introduced into the reactor, the temperature of the reactor is raised to the desired level and VDF (and possibly one or more comonomers) are fed into the reactor, once the first feed of VDF is introduced and the pressure in the reactor has reached the desired pressure, an initiator is introduced to start the polymerization reaction. The polymerization reaction temperature is adjusted according to the characteristics of the initiator used. Once the desired amount of polymer has been reached in the reactor, the monomer feed will be stopped. The residual gas is discharged and the emulsion is recovered from the reactor.

[0025] The surfactant used in the polymerization reaction is any surfactant useful in the PVDF emulsion polymerization reaction in the art, including perfluorinated, partially fluorinated, and non-fluorinated surfactants. Preferably, the surfactant includes a non-fluorinated surfactant. Non-fluorinated surfactants useful in PVDF polymerization reactions include, but are not limited to, oligomers containing polyethylene glycol segments.

[0026] The PVDF of the present invention is obtained by polymerization reaction, and the average particle size of the primary particles of the PVDF obtained by polymerization reaction is 10 to 500 nm, preferably 50 to 300 nm; more preferably 100 to 290 nm. If the average particle size is too small, the cohesive force is too high, and it is not easy to disperse when dispersed with the electrode active material; at the same time, if the particle size is too small, it is easy to block the gaps in the graphite.

[0027] Second, the present invention provides a method for preparing a dry powder mixture containing a conductive agent and PVDF, comprising the steps of spray drying after mixing an aqueous dispersion containing a conductive agent and an aqueous dispersion containing PVDF.

[0028] The aqueous dispersion containing PVDF of the present invention can be a PVDF emulsion, or an aqueous dispersion obtained by dispersing PVDF powder in water under the action of a dispersant or other auxiliary agent. From the perspective of the degree of dispersion and mixing with the aqueous dispersion containing a conductive agent, preferably, the aqueous dispersion containing PVDF is a PVDF emulsion. PVDF emulsion is an emulsion obtained by emulsion polymerization.

[0029] The solid content of the aqueous dispersion containing PVDF of the present invention is 15-30%, preferably, the solid content is 20-25%.

[0030] The solid content of the aqueous dispersion containing the conductive agent of the present invention (ie the content of the conductive agent and the auxiliary agent) is 3-10%, preferably, the solid content is 4-6%.

[0031] The aqueous dispersion containing the conductive agent of the present invention further comprises a dispersant, and the dispersant is used to reduce the surface tension of water and disperse the conductive agent in water.

[0032] The dispersant may be capable of dispersing the conductive agent. Preferably, the dispersant is selected from at least one of sodium dodecyl sulfate (SDS), cetyltrimethylammonium bromide (CTAB), modified polysiloxane, aliphatic polyethylene glycol, and polymethacrylate.

[0033] The amount of the dispersant used is 5-15% of the mass of the conductive agent.

[0034] Furthermore, the aqueous dispersion containing the conductive agent further comprises at least one of an anti-settling agent, a defoaming agent, a thickener, a rheology modifier, a wetting agent, a pH buffer, and a filler.

[0035] The thickener is a water-soluble compound used to increase the viscosity of the dispersion, including but not limited to at least one of polyacrylic acid, polyvinyl alcohol, and methyl cellulose, and the usage amount is 0.1-5% of the mass of the conductive agent.

[0036] The wetting agent is a water-soluble compound used to change the molecular arrangement structure of the interface and accelerate the wetting of the conductive agent, including but not limited to at least one of aliphatic polyethylene glycol copolymerized polypropylene glycol, modified polysiloxane, aliphatic polyol, and glycoside. The amount used is 3-10% of the mass of the conductive agent.

[0037] The defoamer is a semi-water-soluble compound used to reduce foam stability, including but not limited to at least one of polysiloxane and polyethylene glycol copolymerized polypropylene glycol. The amount used is 3-10% of the mass of the conductive agent.

[0038] The buffer is used to adjust the pH value of the aqueous dispersant, and includes but is not limited to at least one of phosphate, amino acid, and amine compounds. The amount used is 0.1-5% of the mass of the conductive agent.

[0039] The average particle size of the aqueous dispersion containing the conductive agent of the present invention is less than 3000 nm; preferably, the average particle size is less than 1500 nm; more preferably, the average particle size is less than 500 nm. Considering the mixing uniformity with the aqueous dispersion containing PVDF, the smaller the average particle size of the aqueous dispersion containing the conductive agent, the more uniformly it can be dispersed.

[0040] The method for preparing the aqueous dispersion containing the conductive agent of the present invention can use a high-speed dispersant, a sand mill, a ball mill and other dispersing equipment to fully mix the conductive agent, water, dispersant and other auxiliary agents.

[0041] As an implementation method, a ball mill is used to mix conductive agent, water, dispersant and other additives. The conductive agent, water and additives are added to a ball milling jar, and zirconium oxide ball milling beads of large, medium and small diameters are added to the ball milling jar. The amount of ball milling beads is 3 to 10 times the mass of water. After the jar is closed, the jar is ground at a speed of 100 to 300 revolutions per minute for 4 to 72 hours.

[0042] The diameter of the large-diameter zirconia ball milling beads is 5 to 10 mm, and the amount used accounts for 10 to 25% of the total mass of the zirconia ball milling beads.

[0043] The diameter of the medium-diameter zirconia ball milling beads is 3-5 mm, and the amount used accounts for 20-35% of the total mass of the zirconia ball milling beads.

[0044] The diameter of the small-diameter zirconia ball milling beads is 1-3 mm, and the amount used accounts for 40-55% of the total mass of the zirconia ball milling beads.

[0045] The mixing of the aqueous dispersion containing the conductive agent and the aqueous dispersion containing PVDF in the present invention can be carried out by using a high-speed dispersant, a sand mill, a ball mill or other dispersing equipment.

[0046] As an implementation mode, the aqueous dispersion containing the conductive agent and the aqueous dispersion containing PVDF are added into a ball mill, and zirconium oxide ball milling beads of large, medium and small diameters are added into the ball mill, and the amount of ball milling beads used is 3 to 10 times the mass of water. After closing the ball mill, the ball mill is ground at a speed of 100 to 300 revolutions per minute for 0.5 to 2 hours.

[0047] The diameter of the large-diameter zirconia ball milling beads is 5 to 10 mm, and the amount used accounts for 10 to 25% of the total mass of the zirconia ball milling beads.

[0048] The diameter of the medium-diameter zirconia ball milling beads is 3-5 mm, and the amount used accounts for 20-35% of the total mass of the zirconia ball milling beads.

[0049] The diameter of the small-diameter zirconia ball milling beads is 1-3 mm, and the amount used accounts for 40-55% of the total mass of the zirconia ball milling beads.

[0050] As an embodiment, the spray drying of the mixture of the aqueous dispersion containing the conductive agent and the aqueous dispersion containing PVDF in the present invention is to atomize the mixture at a speed of 5 to 30 ml / min through a peristaltic pump and a gas pressure of 4 to 6 MPa through a two-fluid spray head under stirring conditions of 10 to 200 revolutions per minute, and then dry it in an environment of 120 to 160°C.

[0051] Thirdly, the present invention provides an application of a dry powder mixture containing a conductive agent and PVDF, wherein the dry powder mixture containing a conductive agent and PVDF is used as a component for preparing an electrode by a dry process.

[0052] As an implementation mode, the dry powder mixture containing the conductive agent and PVDF is mixed with the electrode active material and then electrostatically sprayed onto the metal foil current collector, and hot roller pressed to obtain the electrode.

[0053] As another embodiment, the dry powder mixture containing the conductive agent and PVDF is mixed with PTFE and electrode active materials, the PTFE is fibrillated and hot-pressed by rollers to obtain a self-supporting electrode sheet, and the self-supporting electrode sheet is composited onto a metal foil current collector to obtain an electrode.

[0054] As an embodiment, when the electrode is a positive electrode, the electrode active material is selected from at least one of oxides, sulfides or hydroxides of lithium and transition metals (including but not limited to cobalt, manganese, aluminum, titanium, nickel, iron phosphate, manganese phosphate, etc.), preferably, the electrode active material is selected from at least one of lithium iron phosphate, lithium manganese phosphate, lithium cobaltate, nickel-cobalt-manganese ternary material, lithium-nickel oxide, and lithium-manganese oxide.

[0055] As another embodiment, when the electrode is a negative electrode, the electrode active material is selected from at least one of graphite, artificial graphite, soft carbon (such as coke, etc.), hard carbon, MCNB (mesophase carbon microbeads), disordered carbon, graphene, silicon-containing materials, and carbon-containing and silicon-containing materials. Further, the electrode active material also contains metallic lithium for lithium supplementation.

[0056] Compared with the prior art, the present invention has the following beneficial effects:

[0057] The dry powder mixture containing the conductive agent and PVDF of the present invention is evenly mixed, and has better conductivity (lower resistivity); the particle cohesion is lower, and it can be better mixed with the electrode active material in the dry electrode manufacturing process; during the dry electrode manufacturing, obvious fiberization of PVDF can be seen, and the bonding strength is higher and the bonding sites are more. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 This is a SEM image of the dry powder mixture prepared in Example 1 of the present invention.

[0059] Figure 2 This is a SEM image of the dry powder mixture prepared in Example 2 of the present invention.

[0060] Figure 3 This is a SEM image of the dry powder mixture prepared in Example 3 of the present invention.

[0061] Figure 4 This is a SEM image of the dry powder mixture prepared in Example 4 of the present invention.

[0062] Figure 5 This is a SEM image of the dry powder mixture prepared in Comparative Example 1 of the present invention.

[0063] Figure 6 This is a SEM image of the diaphragm prepared in Example 5 of the present invention. DETAILED DESCRIPTION

[0064] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited to these specific embodiments. Those skilled in the art should recognize that the present invention covers all possible alternatives, improvements and equivalents within the scope of the claims.

[0065] Preparation of PVDF emulsion

[0066] Add 1400g of pure water to a 3.4L polymerization reactor. After the reactor is closed, continue to evacuate with an oil-sealed vacuum pump for 5 minutes, and then backfill with high-purity nitrogen to 0.15MPa. This operation is repeated three times. After the last vacuuming, add vinylidene fluoride (180g) with a high-pressure gas cylinder, add TritonX-100 diluted solution (150g, surface active content 0.1wt%) with a plunger pump, and start stirring (700rpm) to heat the mixture to 80℃. After the temperature stabilizes for 5 minutes, add vinylidene fluoride (100g) with a high-pressure gas cylinder to a pressure of 4.50MPa, and add ammonium persulfate solution (50g, 1wt%) with a plunger pump to initiate the polymerization reaction. During the polymerization reaction, maintain the temperature in the reactor (80±0.5℃), and add vinylidene fluoride to maintain the pressure (4.25±0.25MPa) until the total feeding target of vinylidene fluoride (600g) is reached. Stop stirring and open the pressure relief valve. After the pressure drops to normal pressure, collect the emulsion (2076 g, solid content 20.0 wt%). The average particle size of the obtained polyvinylidene fluoride emulsion is 260 nm by SEM observation. The viscosity of its 7 wt% NMP solution is 1560 Pa.s (shear rate is 2.325 s -1 ).

[0067] Preparation of aqueous dispersion containing conductive agent

[0068] Pure water (0.95 kg), conductive carbon black Super P (50 g), Triton X-100 (5 g), PLURONIC 31R1 (2 g), 10 mm zirconium oxide beads (1 kg), 5 mm zirconium oxide beads (1.5 kg), and 3 mm zirconium oxide beads (2.5 kg) were added to a 3 L ball milling jar and then the jar was closed. After ball milling at 300 rpm for 20 hours on a horizontal ball mill, 0.99 kg of conductive carbon black aqueous dispersion (carbon black SP solid content of 5%) was obtained after filtering through a filter.

[0069] Example 1

[0070] Add grinding balls to a 3L ball mill, the ratio of which is 1 kg of 10mm zirconium oxide grinding balls, 1.5 kg of 5mm zirconium oxide grinding balls, and 2.5 kg of 5mm zirconium oxide grinding balls, add 1 kg of the aqueous dispersion containing carbon black SP prepared above, and add 0.25 kg of the PVDF emulsion prepared above. Place the ball mill on a horizontal ball mill and stir at a speed of 100 rpm for 15 minutes. After filtering the mixed slurry, pass through a two-fluid spray dryer, and the mixed liquid is atomized by a peristaltic pump at a speed of 10 ml / min under a gas pressure of 5 MPa through a two-fluid spray head under stirring conditions of 100 rpm, and then dried in an environment of 150°C to obtain 90g of a dry powder mixture with a D50 of 9.5 μm. The material is dispersed in ethanol and ultrasonicated with a 300w ultrasonic rod for 20 minutes. The D50 after ultrasonic crushing is 1.2 μm, and the resistivity of the dry powder mixture is 1.63×10 -4 Ω·m (under 3MPa pressure), the sphericity D[4,3] / D[3,2] of the dry powder mixture is 1.82.

[0071] Example 2

[0072] The same as Example 1, except that 0.375 kg of the PVDF emulsion prepared above was added to obtain 110 g of dry powder mixture. Its D50 was 10.9 μm. The material was dispersed in ethanol and ultrasonicated for 20 minutes using a 300W ultrasonic rod. The D50 after ultrasonic crushing was 1.8 μm. The resistivity of the dry powder mixture was 1.68×10 -4 Ω·m (under 3MPa pressure), the sphericity D[4,3] / D[3,2] of the dry powder mixture is 1.65.

[0073] Example 3

[0074] The same as Example 1, except that 0.5 kg of the PVDF emulsion prepared above was added to obtain 133 g of dry powder mixture. Its D50 was 9.9 μm. The material was dispersed in ethanol and ultrasonicated for 20 minutes using a 300W ultrasonic rod. The D50 after ultrasonic crushing was 4.5 μm. The resistivity of the dry powder mixture was 2.19×10 -4 Ω·m (under 3MPa pressure), the sphericity D[4,3] / D[3,2] of the dry powder mixture is 1.53.

[0075] Example 4

[0076] The same as Example 1, except that 0.59 kg of the PVDF emulsion prepared above was added to obtain 145 g of dry powder mixture. Its D50 was 10.1 μm. The material was dispersed in ethanol and ultrasonicated for 20 minutes using a 300W ultrasonic rod. The D50 after ultrasonic crushing was 5.5 μm. The resistivity of the dry powder mixture was 2.43×10 -4Ω·m (under 3MPa pressure), the sphericity D[4,3] / D[3,2] of the dry powder mixture is 1.88.

[0077] Comparative Example 1

[0078] 0.25 kg of PVDF emulsion from Zhongnai 2520 was sprayed onto 50 g of conductive carbon black Super P using an ultrasonic atomizer. During spraying, the powder / latex mist was mixed at 180-240 rpm by a magnetic stirring bar. The mist mixture was dried in a vacuum oven at 60°C for 2 hours. The dry mixture was then mixed at 2000 rpm for 1 min in a centrifugal planetary mixer using 5 mm zirconium oxide beads as grinding media to break up large crumbs. The dry powder mixture morphology was observed by SEM. After testing, its D50 was 25.3 μm. The material was dispersed in ethanol and ultrasonicated for 20 minutes using a 300w ultrasonic rod. The D50 after ultrasonic crushing was 24.9 μm, and the resistivity of the dry powder mixture was 13.6×10 -4 Ω·m (under 3MPa pressure), the sphericity D[4,3] / D[3,2] of the dry powder mixture is 5.39.

[0079] Comparative Example 2

[0080] 50g of conductive carbon black Super P and 50g of PVDF powder were mixed in a centrifugal planetary mixer at 100rpm for 15min using 1kg of 10mm zirconia grinding balls, 1.5kg of 5mm zirconia grinding balls, and 2.5kg of 5mm zirconia grinding balls as grinding media. The D50 was tested to be 56.5μm. The material was dispersed in ethanol and ultrasonicated for 20 minutes using a 300w ultrasonic rod. The D50 after ultrasonic crushing was 35.0μm, and the resistivity of the dry powder mixture was 33.8×10 -4 Ω·m (under 3MPa pressure), the sphericity D[4,3] / D[3,2] of the dry powder mixture is 4.46.

[0081] Example 5

[0082] The dry powder mixture (10 g) obtained in Example 1 and lithium iron phosphate powder (90 g) were mixed in a planetary ball mill to obtain an electrode mixed dry powder, which was then pressed in a hot rolling mill to form a self-supporting film. Figure 6 It can be seen that the dry powder mixture prepared in Example 1 can better form a uniform electrode with the electroactive material. At the same time, since the bonding particles are well dispersed, after thermal processing, the bonding particles can form a uniform and continuous bonding fiber network, thereby improving the tablet strength.

Claims

1. A dry powder mixture containing a conductive agent and PVDF, characterized in that: The mass ratio of the conductive agent to PVDF is 1:4 to 4:

1. The resistivity of the dry powder mixture is ≤10 -3 Ω·m, The average particle size D50 of the dry powder mixture is less than 20 μm, After the dry powder mixture is subjected to ultrasonic crushing, the average particle size D50 is less than 7 μm.

2. The dry powder mixture containing a conductive agent and PVDF according to claim 1, characterized in that: The sphericity of the dry powder mixture is D[4,3] / D[3,2]<4.

3. The dry powder mixture containing a conductive agent and PVDF according to claim 1, characterized in that: The resistivity of the dry powder mixture is ≤10 -4 Ω·m.

4. The dry powder mixture containing a conductive agent and PVDF according to claim 1, characterized in that: The average particle size D50 of the dry powder mixture is less than 10 μm. After the dry powder mixture is subjected to ultrasonic crushing, the average particle size D50 is less than 2 μm.

5. The dry powder mixture containing a conductive agent and PVDF according to claim 1, characterized in that: The conductive agent is selected from at least one of carbon black SuperP, multi-walled carbon nanotubes, single-walled carbon nanotubes, graphene, acetylene black, superconducting carbon, Ketjen black, carbon dots, carbon nanofibers, superconducting carbon black, graphite, artificial graphite, carbon, carbon black, activated carbon, and carbon fiber.

6. The dry powder mixture containing a conductive agent and PVDF according to claim 5, characterized in that: The average primary particle size of the conductive agent is 10 to 100 nm.

7. The dry powder mixture containing a conductive agent and PVDF according to claim 1, characterized in that: The PVDF is a VDF homopolymer or a copolymer of VDF and other comonomers. The comonomer is selected from at least one of fluoroethylene, trifluoroethylene, chlorotrifluoroethylene, 1,1-fluorochloroethylene, 1,2-fluorochloroethylene, tetrafluoroethylene, tetrafluoropropylene, pentafluoropropylene, hexafluoropropylene, perfluoroalkylethylene, perfluoroalkylvinyl ether, perfluoro-n-propylvinyl ether, perfluoromethylvinyl ether, perfluoro(2,2-dimethyl-1,3-dioxole), ethylene, acrylic acid, acrylic acid ester, methacrylic acid, methacrylic acid ester, 2-(trifluoromethyl)acrylic acid, 2-(trifluoromethyl)acrylate, 2-trifluoroethyl methacrylate, 1,1-difluoro-2-methyl methacrylate, vinyl ether, vinyl acetate, acrylonitrile, butadiene, isoprene, styrene, maleic anhydride or itaconic acid, The content of VDF structural units in the PVDF is 80-100 mol%.

8. The dry powder mixture containing a conductive agent and PVDF according to claim 1, characterized in that: The solution viscosity of the 7 wt % PVDF NMP solution is 1 to 10000 Pa.s.

9. A method for preparing a dry powder mixture containing a conductive agent and PVDF according to any one of claims 1 to 8, characterized in that: The method comprises the steps of mixing an aqueous dispersion containing a conductive agent and an aqueous dispersion containing PVDF and then spray-drying the mixture.

10. The method for preparing the dry powder mixture containing a conductive agent and PVDF according to claim 9, characterized in that: The aqueous dispersion containing PVDF is a PVDF emulsion.

11. The method for preparing the dry powder mixture containing a conductive agent and PVDF according to claim 9, characterized in that: The average particle size of the aqueous dispersion containing the conductive agent is less than 1500 nm.

12. The method for preparing the dry powder mixture containing a conductive agent and PVDF according to claim 11, characterized in that: The average particle size of the aqueous dispersion containing the conductive agent is less than 500 nm.

13. An application of a dry powder mixture containing a conductive agent and PVDF according to any one of claims 1 to 8, characterized in that: The dry powder mixture containing the conductive agent and PVDF is used as a component for preparing electrodes by dry method.

14. The use of the dry powder mixture containing a conductive agent and PVDF according to claim 13, characterized in that: The dry powder mixture containing the conductive agent and PVDF is mixed with the electrode active material, electrostatically sprayed onto the metal foil current collector, and hot roller pressed to obtain the electrode.

15. The use of the dry powder mixture containing a conductive agent and PVDF according to claim 13, characterized in that: The dry powder mixture containing the conductive agent and PVDF, PTFE and electrode active materials are mixed, the PTFE is fibrillated and hot-pressed by rollers to obtain a self-supporting electrode piece, and the self-supporting electrode piece is composited onto a metal foil current collector to obtain an electrode.

Citation Information

Patent Citations

  • Solvent-free electrode fabrication

    CN113889658A

  • Binder compound, conductive binder, and secondary battery comprising same

    WO2023044754A1